Quality of Life and Well-Being for Residents in Long-Term Care Communities Perspectives on Policies and Practices - Johs-Artisensi, Jennifer L.; Hansen, Kevin E. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explores key factors long-term care recipients have identified as impacting their quality of life and offers programmatic and policy recommendations to enhance well-being within long-term care communities. Leadership and staff who work in nursing homes and other residential care communities serve as gatekeepers to resident well-being, often without recognizing how residents' quality of life is impacted by their decision-making. This book takes a life domain approach to build on research-based studies that document key drivers of care recipients' quality of life, including relationships, autonomy and respect, activities and meals, environment, and care. Using a framework that enhances understanding of resident quality of life, it outlines practical, programmatic, and policy suggestions for long-term care stakeholders, such as administrators, managers, front-line staff, family members, and policy-makers, whose directives and actions impact the lived experience of long-term care residents. As such, this book serves as a roadmap for leaders and managers of long-term care communities, along with policymakers who regulate health and human services, to best structure care environments to maximize quality of life and well-being for long-term care recipients. .
1. Quality of Life in Long-Term Care -- 2. Quality of Life in Long-Term Care -- 3. Relationships with Other Residents, Staff, and Family Members -- 4. Activities and Religious Practices -- 5. Environment and Surroundings -- 6. Food and Dining -- 7. Quality of Care -- 8. Summary, Policy Recommendations, and Conclusions. .
Keywords: Quality of life; Human services; Community development; Social service; Political planning; Quality of Life Research; Social Work Policy; Social Work and Community Development; Policy Evaluation